2013
DOI: 10.1063/1.4813873
|View full text |Cite
|
Sign up to set email alerts
|

Perylenediimide-based distributed feedback lasers with holographic relief gratings on dichromated gelatine

Abstract: One dimensional second-order distributed feedback (DFB) lasers consisting of polystyrene (PS) films doped with a perylenediimide laser dye, deposited over dichromated gelatine (DCG) photoresist layers with solvent resistant relief gratings recorded by holographic lithography, are reported. The advantage of using the grating on DCG in the final device is that the fabrication process is simplified and the grating pattern better preserved, since no etching methods to transfer the grating to another substrate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…with gratings over a DCG layer used as substrate) based on an u-PDI derivative. [7] The device showed a photostability halflife of around 7 min (4200 pump pulses) under constant excitation at around 4 times above its threshold. This value is in accordance with previous ASE measurements [see Overall, this work widens the use of PDIs in laser applications, up to now restricted to bayunsubstituted u-PDIs (all with ASE emission at around 580 nm), by including 1,7-bay bulky substituents in the PDI core.…”
Section: Pdi-1 In the Films Without Getting Pl Quenching Is Also A Rementioning
confidence: 99%
See 2 more Smart Citations
“…with gratings over a DCG layer used as substrate) based on an u-PDI derivative. [7] The device showed a photostability halflife of around 7 min (4200 pump pulses) under constant excitation at around 4 times above its threshold. This value is in accordance with previous ASE measurements [see Overall, this work widens the use of PDIs in laser applications, up to now restricted to bayunsubstituted u-PDIs (all with ASE emission at around 580 nm), by including 1,7-bay bulky substituents in the PDI core.…”
Section: Pdi-1 In the Films Without Getting Pl Quenching Is Also A Rementioning
confidence: 99%
“…[1] Up to now, all reported perylenediimide-based lasers are made of PDIs without substituents at the bay positions (denoted here as u-PDIs, with "u" accounting for bayunsubstituted ), [6][7][8] as a consequence of previous studies on the amplified spontaneous emission (ASE) properties of waveguides containing perylene derivatives with different chemical structures (e.g. imide, anhydride), which concluded that u-PDIs had the best performance.…”
Section: Revised Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Они остаются привлекательными для изготовления ГОЭ, особенно больших размеров, ис-пользуемых в частности для изготовления селективных концентраторов фотовольтаических и фотохимических преобразователей солнечной энергии [9]. Слои бихромированной желатины, содержащие нит-рат серебра, оказались пригодными для получения голо-графическим методом фотонных кристаллов, допирован-ных серебром [10], изготовления рельефных голографи-ческих решеток, используемых в лазерах с распределен-ной обратной связью [11].…”
Section: слои бихромированной желатиныunclassified
“…Resonators for geometry (c) devices, based on either dichromated gelatine (DCG) or dichromated poly(vinyl alcohol) (DCPVA) photoresist layers deposited over FS, were fabricated as previously described. 21,22 Resonators for geometry (a) devices were prepared by thermal-NIL and subsequent etching on either FS or SiO 2 layers grown by thermal oxidation of silicon wafers, 23 or by HL and etching on glass.…”
Section: Methodsmentioning
confidence: 99%